Does a Contractionary Monetary Policy in Turkey Stabilise Food Inflation? - Oğuz Tümtürk (İktisat Politikası Araştırmaları Dergisi)
This study analyzes the impact of the monetary policy in Turkey on domestic food inflation. We statistically show that contractionary monetary policies produce positive asymmetric impacts and destabilise food inflation. This result shows that the cost channel of the monetary transmission mechanism prevails over the demand channel of the monetary transmission mechanism. We also provide empirical evidence that an increase in energy and world food prices also drives domestic food inflation. These results are robust with respect to employing different control variables, the estimation of the model with different data sets, and the structural breaks that occurred during the study period.